Avaliação do perfil de metilação nas diferentes formas clínicas do líquen plano bucal - Aline Fernanda Cruz (2017)
The oral Lichen Planus is a chronic disease of great clinical relevance. Although its etiology is not well understood, data suggests that its inflammatory events are mediated by T lymphocytes. Identifying the epigenetic mechanisms involved in the pathogenesis of oral Lichen Planus is essential to understanding the inflammatory reaction that occurs in the disease. Therefore, this work evaluated the methylation profile in different clinical forms of oral Lichen Planus. The patients included in the study were divided into three groups: reticular/ plaque lichen planus and erosive lichen planus. For the control group, a sample of normal mucosa was collected in patients submitted to extraction of included teeth. In order to evaluate the methylation profile, the DNA was extracted from the samples and then they were grouped into 3 pools referring to their respective groups. The levels of methylation of genes related to the development of the inflammatory response were evaluated. The pools were digested by methylation-sensitive and methylation-dependent enzymes. The digested samples were submitted to a real-time polymerase chain reaction (qRT-PCR) and through the CT values, the relative percentage of methylated DNA for each gene in each group was obtained. The percentage of methylation found in the STAT5A promoter region in the normal mucosa (59.05%) showed the greatest discrepancy when compared to reticular/plaque and erosive oral Lichen Planus (5.43% and 2.76%, respectively). When comparing reticular/plaque lichen planus with erosive, the gene ELANE presented hypermethylation in the promoter region of the gene in the reticular/plaque Lichen Planus (72.16%) compared to the erosive form (50.00%). Based on the results it is possible to conclude that methylation of the genes responsible for inflammation in oral Lichen Planus differs with the normal mucosa and among the clinical types of the disease.